Muscle Ultrasonographic Elastography in Children: Review of the Current Knowledge and Application - Agnieszka Cebula (MDPI AG, 2021)
Ultrasonographic elastography is a relatively new imaging modality for the qualitative and quantitative assessments of tissue elasticity. While it has steadily gained use in adult clinical practice, including for liver diseases, breast cancer, thyroid pathologies, and muscle and tendon diseases, data on its paediatric application is still limited. Moreover, diagnosis of muscular diseases in children remains challenging. The gold standard methods, namely biopsy, electroneurography, and electromyography, are often limited owing to their invasive characteristics, possible contraindications, complications, and need for good cooperation, that is, a patient’s ability to perform certain tasks during the examination while withstanding discomfort, which is a significant problem especially in younger or uncooperative children. Genetic testing, which has broad diagnostic possibilities, often entails a high cost, which limits its application. Thus, a non-invasive, objective, repeatable, and accessible tool is needed to aid in both the diagnosis and monitoring of muscle pathologies. We believe that elastography may prove to be such a method. The aim of this review was to present the current knowledge on the use of muscle elastography in the paediatric population and information on the limitations of elastography in relation to examination protocols and factors for consideration in everyday practice and future studies.